A Smart Multifunctional Nanoparticle for Enhanced Near-Infrared Image-Guided Photothermal Therapy Against Gastric Cancer - Shao, Jun (Int J Nanomedicine, 2021)
BACKGROUND: Surgery is considered to be a potentially curative approach for gastric cancer. However, most cases are diagnosed at a very advanced stage for the lack of typical symptoms in the initial stage, which makes it difficult to completely surgical resect of tumors. Early diagnosis and precise personalized intervention are urgent issues to be solved for improving the prognosis of gastric cancer. Herein, we developed an RGD-modified ROS-responsive multifunctional nanosystem for near-infrared (NIR) imaging and photothermal therapy (PTT) against gastric cancer. METHODS: Firstly, the amphiphilic polymer was synthesized by bromination reaction and nucleophilic substitution reaction of carboxymethyl chitosan (CMCh) and 4-hydroxymethyl-pinacol phenylborate (BAPE). Then, it was used to encapsulate indocyanine green (ICG) and modified with RGD to form a smart multifunctional nanoparticle targeted to gastric cancer (CMCh-BAPE-RGD@ICG). The characteristics were determined, and the targeting capacity and biosafety were evaluated both in vitro and in vivo. Furthermore, CMCh-BAPE-RGD@ICG mediated photothermal therapy (PTT) effect was studied using gastric cancer cells (SGC7901) and SGC7901 tumor model. RESULTS: The nanoparticle exhibited suitable size (≈ 120 nm), improved aqueous stability, ROS-responsive drug release, excellent photothermal conversion efficiency, enhanced cellular uptake, and targeting capacity to tumors. Remarkably, in vivo studies suggested that CMCh-BAPE-RGD@ICG could accurately illustrate the location and margin of the SGC7901 tumor through NIR imaging in comparison with non-targeted nanoparticles. Moreover, the antitumor activity of CMCh-BAPE-RGD@ICG-mediated PTT could effectively suppress tumor growth by inducing necrosis and apoptosis in cancer cells. Additionally, CMCh-BAPE-RGD@ICG demonstrated excellent biosafety both in vitro and in vivo. CONCLUSION: Overall, our study provides a biocompatible theranostic nanoparticle with enhanced tumor-targeting ability and accumulation to realize NIR image-guided PTT in gastric cancer.